New and rare diatom (Bacillariophyta) species from a mountain lake in Eastern Siberia - Potapova, Marina; Hamilton, Paul; Kopyrina, Lyubov; Sosina, Nadezhda (Phytotaxa, 2014)
The examination of a moss sample collected from a lake in a remote mountainous region of Eastern Siberia revealed a diverse diatom flora that included four new species: Eunotia frigida, Brachysira subtile, Encyonopsis vasilievae, and Neidium rugosum. N. rugosum has been previously illustrated from several locations in the arctic and subarctic and is widely distributed across the circumpolar Arctic. The distribution of three other species is likely more limited. Besides these species, a number of rare diatoms were also found in the moss community. These include Neidium boyeri and Stauroneis crassula previously known only from North America; Encyonema sibericum so far only reported from Western Siberia, Encyonema lunatum var. borealis earlier found in Finland, and Eunotia ferefalcata, Pinnularia angustarea, and Naviculadicta mongolica so far reported only from Mongolia. This study contributes to the understanding of biogeographic patterns of diatom distribution.